Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(=\frac{16}{5}.\frac{15}{16}-\left(\frac{3}{4}+\frac{2}{7}\right):\left(\frac{-29}{28}\right)\)
\(=3-\left(\frac{21}{28}+\frac{8}{28}\right):\left(\frac{-29}{28}\right)\)
\(=3-\left(\frac{29}{28}\right).\left(\frac{-28}{29}\right)\)
\(=3-\left(-1\right)\)
\(=4\)
b) \(=\left(\frac{1}{4}+\frac{25}{2}-\frac{5}{16}\right):\left(12-\frac{7}{12}:\left(\frac{3}{8}-\frac{1}{12}\right)\right)\)
\(=\left(\frac{4}{16}+\frac{200}{16}-\frac{5}{16}\right):\left(12-\frac{7}{12}:\left(\frac{3.3}{2.3.4}-\frac{2}{2.3.4}\right)\right)\)
\(=\left(\frac{199}{16}\right):\left(12-\frac{7}{12}:\left(\frac{9}{24}-\frac{2}{24}\right)\right)\)
\(=\frac{199}{16}:\left(12-\frac{7}{12}.\frac{24}{7}\right)\)
\(=\frac{199}{16}:\left(12-2\right)\)
\(=\frac{199}{16}:10\)
\(=\frac{199}{160}\)
c) \(\left(\frac{-3}{5}+\frac{5}{11}\right):\frac{-3}{7}+\left(\frac{-2}{5}+\frac{6}{5}\right):\frac{-3}{7}\)
\(\left(\frac{-33}{55}+\frac{25}{55}\right):\frac{-3}{7}+\left(\frac{4}{5}\right):\frac{-3}{7}\)
\(\left(\frac{-8}{55}\right).\frac{-7}{3}+\frac{4}{5}.\frac{-7}{3}\)
\(\frac{-7}{3}\left(\frac{-8}{55}+\frac{4}{5}\right)\)
\(\frac{-7}{3}.\frac{36}{55}=\frac{-84}{55}\)
a)\(\frac{x+1}{5}+\frac{x+3}{4}=\frac{x+5}{3}+\frac{x+7}{2}\)
\(\Leftrightarrow\frac{12\left(x+1\right)}{60}+\frac{15\left(x+3\right)}{60}=\frac{20\left(x+5\right)}{60}+\frac{30\left(x+7\right)}{60}\)
\(\Leftrightarrow12x+12+15x+45=20x+100+30x+210\)
\(\Leftrightarrow27x+57=50x+310\)
\(\Leftrightarrow27x+57-50x-310=0\)
\(\Leftrightarrow-23x-253=0\)
\(\Leftrightarrow x=-\frac{253}{23}\)
b)Tự làm
\(\frac{3}{2}:\left(x-\frac{5}{3}\right)-\frac{17}{3}=\frac{11}{3}\)
<=> \(\frac{3}{2}:\left(x-\frac{5}{3}\right)=\frac{28}{3}\)
<=> \(x-\frac{5}{3}=\frac{9}{56}\)
<=> \(x=1\frac{139}{168}\)
Vậy...
\(\frac{3}{2}:\left(x-\frac{5}{3}\right)-\frac{17}{3}=\frac{11}{3}\)
\(\frac{3}{2}:\left(x-\frac{5}{3}\right)=\frac{11}{3}+\frac{17}{3}\)
\(\frac{3}{2}:\left(x-\frac{5}{3}\right)=9\)
\(\left(x-\frac{5}{3}\right)=\frac{3}{2}:9\)
\(x-\frac{5}{3}=\frac{1}{6}\)
\(x=\frac{1}{6}+\frac{5}{3}=\frac{11}{6}\)